Improved Academic Performance and Student Perceptions of Learning Through Use of a Cell Phone‐Based Personal Response System. Issue 1 (5th January 2018) - Ma, Sihui; Steger, Daniel G.; Doolittle, Peter E.; Stewart, Amanda C.
Abstract: Personal response systems, such as clickers, have been widely used to improve the effectiveness of teaching in various classroom settings. Although hand‐held clicker response systems have been the subject of multiple prior studies, few studies have focused on the use of cell phone‐based personal response system (CPPRS) specifically. This study explores students' academic performance and their perceptions of learning through the use of a CPPRS (TopHat) in an undergraduate Food Science class. In this study, students did not use the CPPRS during the first half of the semester‐long course, but did during the second half. When CPPRS was used, students responded to 2 multiple‐choice questions at 3 points during the class, (a) at the beginning of class, (b) in the middle of the class, and (c) at the end of the class. Student performance was measured by correctness rates on eight 10‐item multiple choice quizzes, 4 quizzes each covering the class content that was delivered with compared with without CPPRS. A survey was conducted at the end of the semester asking ( n = 28) students' perceptions of CPPRS. The average correctness rate for quizzes covering content delivered with CPPRS (85% ± 9%) was significantly higher than for content delivered without CPPRS (82% ± 10%) ( P = 0.016). In addition, students perceived that CPPRS was easy to use (5.04 ± 0.58 on a 1 to 6 scale with 1 being strongly disagree and 6 being strongly agree) and positively impacted their learning (4.52 ± 0.99 using the same scale). When used correctly, CPPRS can facilitate student learning in lectures.